Quality of life after Brooke ileostomy and ileal pouch-anal anastomosis. Comparison of performance status. - Pemberton, J H (1989)
Although the clinical results of Brooke ileostomy are good, patients are permanently incontinent of stool and gas. Alternative operations designed to restore enteric continence, such as ileal pouch-anal anastomosis, must not only be as safe and effective as Brooke ileostomy, but should provide an improved quality of life in order to establish long-term acceptability. Ileal pouch-anal anastomosis has been performed safely and good functional results have been reported. The quality of life after ileal pouch-anal anastomosis, however, has not been documented. Two hundred ninety-eight ileal pouch patients and 406 Brooke ileostomy patients who had the operations performed for chronic ulcerative colitis or familial adenomatous polyposis formed the basis of the study. After adjusting for age, diagnosis, and reoperation rate, logistic regression analysis of performance scores in seven different categories was used to discriminate between operations. Median follow-up was longer in Brooke ileostomy patients than in ileal pouch patients (104 months vs. 47 months, respectively), and Brooke ileostomy patients were slightly older (38 years vs. 32 years). A great majority of patients in each group were satisfied (93% Brooke ileostomy; 95% ileal pouch-anal anastomosis). Thirty-nine per cent of Brooke ileostomy patients, however, desired a change in the type of ileostomy they had. At 47 months, ileal pouch patients had a median of 5 stools per day and 1 at night, 77% did not experience any daytime incontinence, while 22% reported occasional spotting. In each performance category, the performance score discriminated between operations, with the probability of having had an ileal pouch-anal anastomosis operation increasing with improvement in performance scores (p less than 0.05). We concluded that after ileal pouch-anal anastomosis, patients experienced significant advantages in performing daily activities compared to patients with Brooke ileostomy and thus may experience a better quality of life. These results help further to establish ileal pouch-anal anastomosis as a safe, attractive, and valid alternative to Brooke ileostomy.